2022
DOI: 10.1088/1755-1315/1112/1/012098
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of the drying process of mulberry fruits by infrared radiation

Abstract: In this study, drying time, drying rate and applicability of some existing drying models of mulberry fruits white mulberry (M.Alba) and black mulberry (M.Nigra) dried at different temperatures and infrared power were investigated. A laboratory-type infrared dryer was used in the study, and mulberry fruit samples were dried at 70 and 75 °C and at 180 and 210 W. Page, Modified Page, Henderson and Pabis, Logarithmic, Binary and Binary Exponential samples were used to determine the drying kinetics. When the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The reduced thickness and thin layer of the turmeric slices attribute to the absence of constant rate period for the IR drying of the turmeric slices (Jeevarathinam et al, 2021). Matouk et al (2019), Tarawade et al (2022), Osae et al (2020), and Pei et al (2022) also reported similar results on the IR drying of grapes, mulberry, and ginger.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The reduced thickness and thin layer of the turmeric slices attribute to the absence of constant rate period for the IR drying of the turmeric slices (Jeevarathinam et al, 2021). Matouk et al (2019), Tarawade et al (2022), Osae et al (2020), and Pei et al (2022) also reported similar results on the IR drying of grapes, mulberry, and ginger.…”
Section: Resultsmentioning
confidence: 60%
“…The incidence of falling rate period indicates that the drying rate depends on the diffusion of the moisture from inside of the food product to its surface(Akpinar & Toraman, 2016;Manikantan et al, 2022). The reduced thickness and thin layer of the turmeric slices attribute to the absence of constant rate period for the IR drying of the turmeric slices(Jeevarathinam et al, 2021) Matouk et al (2019),Tarawade et al (2022),Osae et al (2020), andPei et al (2022). also reported similar results on the IR drying of grapes, mulberry, and ginger.…”
mentioning
confidence: 67%
“…The activation energy is calculated using the slope of the 𝐼𝑛 𝐷 1/𝑇 plot shown in figure 3. Some activation energies calculated for gourd in the literature are as follows: 50.06 kJ/mol [9] and 34.7 ± 0.073 kJ/ mol [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…The first metallogenic generalizations also refer to this period (H.M.Abdullaev, A.V.Korolev, I.H.Khamrabaev, etc.) [25,26]. The second stage (1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975) is characterized by numerous discoveries of small occurrences but, at the same time, a general decrease in the growth of reserves of tungsten ores, which is due to conjunctural reasons and the exhaustion of the fund of traditional skarnogenetic types of mineralization.…”
Section: Methodsmentioning
confidence: 99%